2021
DOI: 10.1080/10413200.2021.1884918
|View full text |Cite
|
Sign up to set email alerts
|

Pathway decisions during the student-athlete transition out of university in the United Kingdom

Abstract: The student-athlete transition out of university requires athletes to make important decisions regarding their future. However, there is no research that focuses on the pathways that athletes take when they leave university and the factors that underpin athletes' decisions. The current study explored the pathways athletes take when they leave university in the United Kingdom (UK), and their reasons for taking these specific routes. Eleven elite UK former and current university student-athletes (Mage = 21.4) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…It is also important to note that athletes who did not receive any type of scholarship had higher expectations of continuing their athletic career after completing their studies as compared to those who received a scholarship. Vickers and Morris (2021) indicated that student-athletes who finished university took different paths, one of which was to continue with their sports full time, which is consistent with the results obtained in the present research. It is possible that these results are due to the fact that athletes who had received previous aid showed higher levels of academic and sporting demands than athletes without scholarships, which favors the appearance of burnout syndrome in these athletes and hinders their continuity in sports, opting to completely devote themselves to the world of work once they have finished their studies ( Judge et al, 2012 ; Åkesdotter et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…It is also important to note that athletes who did not receive any type of scholarship had higher expectations of continuing their athletic career after completing their studies as compared to those who received a scholarship. Vickers and Morris (2021) indicated that student-athletes who finished university took different paths, one of which was to continue with their sports full time, which is consistent with the results obtained in the present research. It is possible that these results are due to the fact that athletes who had received previous aid showed higher levels of academic and sporting demands than athletes without scholarships, which favors the appearance of burnout syndrome in these athletes and hinders their continuity in sports, opting to completely devote themselves to the world of work once they have finished their studies ( Judge et al, 2012 ; Åkesdotter et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…We are aware that the sample size is a limitation of our study. However, participants are elite and Olympic athletes, and the sample is comparable to other similar studies on elite athletes’ DC ( Tshube and Feltz, 2015 ; Defruyt et al, 2020 ; Moreno et al, 2021 ; Vickers and Morris, 2021 ).…”
Section: Methodssupporting
confidence: 55%
“…Moreover, when studying (former) international elite athletes, authors should consider that sample size issues are common; therefore, it might be difficult to include a sufficient number of athletes into the study ( Küttel, 2017 ). Further research is needed to explore the pathways athletes take when they leave university ( Vickers and Morris, 2021 ) and how we refer to people engaging in DC ( Geary et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the quality of post-sport career transitions is associated with pre-retirement preparation, such as education and financial support (Robnik et al, 2022). Several studies have explored the dual career paths of student-athletes, examining their engagement with university majors, plans for dual careers, and the demands encountered during such transitions (Condello et al, 2019;Vickers and Morris, 2022). This line of inquiry extends to employed Olympic athletes, providing insights into dual career support and its effect on the quality of transitions (Robnik et al, 2022).…”
Section: Introductionmentioning
confidence: 99%